Possibilities of reducing the specific cost of thermoelectric generator energy converters - Lysko, V.V.; Konstantynovych, I.A.; Kuz, R.V.; Derevianko, T.V. (Journal of Thermoelectricity, 2024)
The paper presents the results of computer simulation of a thermoelectric generator module for waste heat recovery. The influence of the module leg height on its energy and economic indicators is analyzed. Bibl. 11, Fig. 15.